Clinical Outcomes for Systemic Corticosteroids Versus Vincristine in Treating Kaposiform Hemangioendothelioma and Tufted Angioma. Issue 20 (May 2016) - Liu, Xiaohan; Li, Jiaying; Qu, Xinhua; Yan, Weili; Zhang, Ling; Zhang, Shanyong; Yang, Chi; Zheng, Jiawei
Abstract : Abstract: A meta-analysis was performed to evaluate the efficacy and safety of systemic corticosteroids versus those of vincristine in the treatment of kaposiform hemangioendothelioma (KHE) and tufted angioma (TA). A literature search of PubMed, Embase, and Web of Science was performed for clinical studies on systemic corticosteroid versus vincristine therapies in treating KHE/TA. Pooled relative risks (RRs) and response rate with 95% confidence intervals (CIs) were used to measure outcomes. Heterogeneity, subgroup analysis, sensitivity analysis, and publication bias analysis were performed for result evaluation. Thirteen studies, comprising 344 participants, were used in the analysis. Vincristine therapy was found to be relatively more effective than systemic corticosteroids (RRs = 0.45, 95%CI: 0.35–0.58). The result of pooled adverse reactions response rate for systemic corticosteroids was 0.31 (95%CI, 0.18–0.43), significantly higher than that for vincristine, which was 0.12 (95%CI, 0.06–0.19). In subgroup analyses, factors including mean age and race of patients, and period of follow-up were examined as possible sources of heterogeneity. This is the first meta-analysis estimating the clinical outcomes of systemic corticosteroids in comparison with those of vincristine in the treatment of KHE/TA. The results showed that vincristine was considerably more effective with lower complication rates than systemic corticosteroids; thus, vincristine could be suggested as the first-line therapy for KHE/TA.